The lobster [videorecording (DVD)] - Lanthimos, Yorgos, 1973-; Farrell, Colin, 1976-; Weisz, Rachel, 1970-; Seydoux, Léa, 1985-; Reilly, John C., 1965- (Lionsgate, 2016)
In a dystopian near future, single people, according to the laws of The City, are taken to The Hotel, where they are obligated to find a romantic partner in forty-five days or are transformed into beasts and sent off into The Woods.